Intercultural musical dialogue in St John Passion by Sofia Gubaidulina - Stochniol, Magdalena (Interdisciplinary Studies in Musicology, 2020)
Sofia Gubaidulina is one of the most important composers living today. Among her many works acknowledged and awarded prizes on the international forum, the diptych St John Passion and St John Easter [The Resurrection of Christ according to St John], the opus magnum of that outstanding Russian composer, occupies a special place. This work focuses the most important features of her music, such as a profound theological message based on a compilation of fragments from the Old Testament, Gospels and the Apocalypse of St John, as well as her musical rootedness in the cultural tradition of the churches of both East and West. Gubaidulina adapts the achievements of the artistic avant-garde in new and original ways, while at the same time she is an ardent champion of traditional universal values grounded in the message of the Bible and Christian cultural tradition. This paper presents St John Passion by Sofia Gubaidulina in the context of its theological and intercultural dialogue, as well as attempting to characterise the phenomenon represented by this composer, who raises anew reflection on the fate of humankind in the context of existential questions, while remaining faithful to the idea of high art, exquisite and open to various understandings of the idea of beauty.